Photos can speak: The farmer’s perspective of livestock - International Livestock Research Institute (International Livestock Research Institute, 2022)
The ‘Livestock-led interventions towards equitable livelihoods and improved environment in the Northwest Highlands of Vietnam’ or Li-chăn project used the ‘photovoice’ for monitoring and evaluation.